EFEKTIVITAS PENYALURAN BANTUAN LANGSUNG TUNAI BAGI MASYARAKAT TERDAMPAK COVID-19 - Moshavi, Sophia; Fitriana, Nur; Yauri, Kelvin (Media Akuntansi dan Perpajakan Indonesia, 2022)
This research was conducted to analyze the effectiveness of the government’s distribution of the Direct Cash Aid, because in practice, the processes and procedures for the distribution of these social assistance fundsare too complicated and overlapping, the data used are inaccurate, furthermore, there are a large number of state officials who misuse the Direct Cash Aid for personal gain. This research uses a qualitative approach by analyzing the social phenomena that occurs. The method used in this research is netnography. Data collection in this study was carried out with a lurking approach, using the internet, social media, and online news as data sources. The result of this research is that the distribution of the Direct Cash Aid funds has not been completely effective.